Effects of an entire season on physical fitness in elite female handball players - Granados, C.; Izquierdo, M.; Ibanez, J.; Ruesta, M.; Gorostiaga, E. M. (Medicine & Science in Sports & Exercise, 2008)
Purpose: Sixteen elite female handball players were studied to examine the effects of an entire season on anthropometric characteristics, physical fitness, and throwing velocity.